2006
DOI: 10.1080/02640410500457117
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a complex training and detraining programme on selected strength and power variables in early pubertal boys

Abstract: Complex training, a combination of resistance training and plyometrics is growing in popularity, despite limited support for its efficacy. In pre- and early pubertal children, the study of complex training has been limited, and to our knowledge an examination of its effect on anaerobic performance characteristics of the upper and lower body has not been undertaken. Furthermore, the effect of detraining after complex training requires clarification. The physical characteristics (mean+/-s) of the 54 male partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
116
3
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 20 publications
6
116
3
14
Order By: Relevance
“…Despite reports that resistance and/or general physical training can enhance muscle strength in children, there are conflicting reports as to whether these benefits translate into improvements in other physical performance tasks (athletic performance, VJH, long jump, sprint speed) (Faigenbaum et al 1999;Ingle et al 2006;Lillegard et al 1997;Weltman et al 1986). When we examined the effect of the intervention on VJH in the girls, there was a marked improvement in the exercise relative to control group (12.5 versus 3.2% per year), but the between group difference did not persist after adjusting for baseline age and VJH and organised physical activity outside of school at follow-up [mean adjusted difference, 4.1% (95% CI: -3.7, 12.0)].…”
mentioning
confidence: 99%
“…Despite reports that resistance and/or general physical training can enhance muscle strength in children, there are conflicting reports as to whether these benefits translate into improvements in other physical performance tasks (athletic performance, VJH, long jump, sprint speed) (Faigenbaum et al 1999;Ingle et al 2006;Lillegard et al 1997;Weltman et al 1986). When we examined the effect of the intervention on VJH in the girls, there was a marked improvement in the exercise relative to control group (12.5 versus 3.2% per year), but the between group difference did not persist after adjusting for baseline age and VJH and organised physical activity outside of school at follow-up [mean adjusted difference, 4.1% (95% CI: -3.7, 12.0)].…”
mentioning
confidence: 99%
“…Increased SMM in group M may also explain the significant between-group differences in P max and other AAP variables found in our study. Strength and power development during puberty is known to be influenced by the linear increase of skeletal muscle size and mass [5,[36][37][38]. Even a slight increase in SMM in males before puberty can raise their work efficiency [39].…”
Section: Discussionmentioning
confidence: 99%
“…Some tests which are considered challenging task for subjects such as 1RM test and the Wingate anaerobic test were found to be feasible for young male Thai athletes. The Wingate anaerobic test has also been used to measure anaerobic power from effect of complex training program on early pubescent boys [11]. Likewise, 1RM protocol was also used to measure maximum strength in adolescent soccer players before and after 16 weeks of resistance training program [4].…”
Section: Discussionmentioning
confidence: 99%
“…The training programs for this study were based on available data sources [4,11,13,24,25] that used both children and adolescents who were either non-athletes or athletes. As our resistance training programs were predominantly designed to evaluate how young Thai male athletes respond to the program, subjective information revealed that young Thai male athletes were highly capable of performing all exercise routines throughout the two weeks of study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation